Comparative Evaluation of the Polar Organic Chemical Integrative Sampler in Two Types of Validation Systems Simulating Peak Concentration Events. (27th September 2021) - Noro, Kazushi; Vermeirssen, Etiënne L.M.; Banno, Arisa; Ono, Junko; Yabuki, Yoshinori
Abstract: Polar organic chemical integrative sampler (POCIS) devices have been suggested for measuring time‐weighted averages (TWAs) of contaminant concentrations resulting from chemical leak accidents in aquatic environments. However, the response of the POCIS device in the emergency condition in natural water remains unclear. The response of the POCIS device to contaminant fluctuation was investigated using a chamber test with tap water and a channel test with natural water. The fluctuation in the chamber and the channel simulated the condition of river water under a chemical leak scenario (maximum concentration: 1–10 μg L –1, half‐life: 1 day). The target chemicals were neonicotinoid pesticides (dinotefuran, clothianidin, thiamethoxam, imidacloprid, acetamiprid, and thiacloprid) and bisphenol A. The ratio of the POCIS measured value to the TWA values of grab samplings (POCIS/TWA) for the channel test (temperature: 15 °C, flow velocity: 15 cm s –1 ) ranged from 61% (clothianidin) to 133% (thiacloprid). The results indicated that the POCIS device could be effectively used as a monitoring device in an aquatic environment under the chemical leak scenario over a time period of more than14 days. In addition, the POCIS/TWA ratios obtained from the chamber test and the channel test were in the range of 50–150%. Thus, the chamber test could be used to evaluate the POCIS device at a low cost. Environ Toxicol Chem 2021;40:3010–3018. © 2021 SETAC